The role of the arts on community mental health and cultural understanding in Addis Ababa, Ethiopia - Hearst, Mary O.; Belay, Melaku; Wilcox, Hui (Frontiers in Public Health, 2023)
Background: There are rising rates of depression and anxiety in low- and middle-income countries. In Ethiopia, rates were rising before the COVID-19 pandemic and the country faces ethnic discord and armed conflict. Novel community based strategies are needed to improve mental health and cultural unity. The purpose of this research is to describe the role a cultural center’s art programming on mental health and cultural unity. Methods: This qualitative study conducted interviews and focus groups with audience members, artists, and staff at Fendika Cultural Center, Addis Ababa, in January 2023. Participants were recruited via word of mouth and purposive sampling. Focus groups and interviews led in English or Amharic, recorded, transcribed and translated as needed. Questions included participant experiences with Fendika Cultural Center and how experiencing the arts at Fendika influences well-being. We used deductive analysis, guided by the Arts and Culture in Public Health Framework. Results: Two focus groups (n=11 participants, 5 female, 6 males) and five key informant interviews (3 females, 2 males) were completed. Findings suggested that the activities at Fendika were important for addressing individual depression and anxiety by the social and physical environment as well as the inherent cultural support and unity expressed through the arts. The themes were consistent with the Arts and Culture in Public Health Framework . Conclusion: The arts play an important role in positive mental health and cultural unity. Further research is needed to establish the generalizability, reach, and persistence of the impact of cultural centers on mental health cultural understanding.